Metode Lean Construction dalam Pengendalian Limbah Material pada Pekerjaan Struktur Baja di Proyek Gedung Makodim 521 Kota Kediri - Farhan Maulana Ivo; Sony Susanto (Universitas Batanghari Jambi, 2026)
The construction industry contributes significantly to infrastructure development but faces major challenges in the form of material inefficiency that generates construction waste. Studies show that an average of 5–15% of materials are wasted during project execution, increasing costs, causing delays, and having a negative impact on the environment. The construction project of the Makodim 521 Building in Kediri City was chosen as the research object because it involves the use of WF steel structures, CNP purlins, and Onduvilla roof coverings with high costs and significant waste potential. Initial analysis revealed that eight materials contributed more than 80% of the total roofing work cost, with the highest waste level of 2.32% found in Onduvilla roof coverings and the largest absolute waste volume of 27.14 kg in CNP profile purlins. This research aims to develop a data-based waste control strategy using the Lean Construction approach. The methods used include material identification, Pareto analysis to determine priority materials, calculation of waste levels, and analysis of the causes of waste. The strategies designed include the implementation of Just in Time (JIT), worker training, design optimization with Building Information Modeling (BIM), application of the 5S principles, as well as utilization and recycling of leftover materials. The results show that the implementation of these strategies has the potential to reduce waste by up to 38%, reduce excess stock by 30%, and reuse up to 50% of leftover materials. The main contribution of this research is to provide a measurable waste control strategy framework that can be directly implemented to improve project efficiency and support sustainable construction practices in Indonesia and other developing countries.